O controle interno na gestão pública municipal: um estudo multicaso em municípios de pequeno porte do estado de Goiás - (:unkn) unknown (Universidade Federal de Goiás, 2019)
The Federal Constitution of 1988 required the implementation of the internal control system in the three powers, reaffirming the need to maintain the internal control system intergrated by Brazilian municipalities. Thus, this research aims to diagnose the internal control structure implemented in the municipalities surveyed and propose suggestions for improvement in accordance with legal requirements, in order to meet the local reality. Therefore, we chose to research multiple cases, using an intentional sample, totaling four small cities in Goias, with an estimated population of up to 50,000 inhabitants. A descriptive, qualitative approach was performed, data were collected through semi-structured interviews, document analysis, questionnaire application and participant observation. Observations, interviews and application of the questionnaire were conducted between July and November 2019, with visits to those responsible for the central internal control agencies of the municipalities. The main documents analyzed were: laws, decrees, normative procedures, normative instructions, resolutions, LOA, LDO, PPA, balance sheets, balance sheets, among others. Data were analyzed through content analysis. For each specific objective was defined a category and the respective elements of analysis. Regarding the administrative organization, there is the absence of specific legal instruments at the municipal level. Regarding the hierarchy, the interviewees declared to be subordinate to the highest manager (mayor), or have secretarial status, as directed by the literature. Regarding the nomenclature, there was a diversity of terms used, this is due to the fact that there is no standardization by the legislation. It is noticed a limited scope and performance and low number of employees involved, revealing little understanding about the activities and control procedures. To verify the performance of these internal control bodies, we sought to list some of the main development activities based on the researcher's experience, namely: bidding, asset control, warehouse management and annual closing of government accounts and management accounts. With regard to bidding, it appears that the municipalities do not perform preventive controls in the internal and external phases of the bidding process. With regard to asset control, respondents revealed that the municipality outsources wealth management. All respondents are unanimous in revealing that there is no physical warehouse in their prefectures. As for the appreciation of government accounts and management accounts, revealed to leave to the accounting industry. Regarding the classification of the functions performed by the respective organs and the activities disciplined by the FC: accounting, financial, budgetary, operational and patrimonial supervision, it is verified that none of the four prefectures perform the five main activities by the Federal Constitution. Regarding the maturity level of the internal control structure, the four municipalities were classified at the incipient level (0). Thus, it is expected that the surveyed municipalities institutionalize their internal control system through specific municipal laws, adopt new control practices, procedures and activities, in order to comply with local legislation and reality.
Internal control in municipal public management: a multi-case study in small municipalities of the state of Goiás
Keywords: Controle interno; Administração pública; Municípios; Atividades de controle; Internal control; Public administration; Counties; Control activities; ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS